2009
DOI: 10.1002/sdr.423
|View full text |Cite
|
Sign up to set email alerts
|

Simulating urban transformation in Haaglanden, the Netherlands

Abstract: This paper describes a group model-building project about new housing construction, urban renewal and the impact of both processes on a regional social housing market. A team of seven stakeholders participated in model construction over a 1-year period. The paper addresses the modeling process, model analysis and policy experiments. The model yielded several counterintuitive insights, helped the stakeholders to settle a contentious issue and was used in fl ight simulator workshops with managers and policy make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…There are many examples of system dynamics models being developed using the group model building approach, for instance, for business development , for new housing development and urban renewal (Eskinasi et al, 2009) and for integrated sustainability assessments (Videira et al, 2010). Alongside these case studies, there has been a continuing focus on methodological developments, drawing upon the accumulated experience of many years of case study work Rouwette, 2011).…”
Section: Facilitated Modelling and Simulationmentioning
confidence: 99%
“…There are many examples of system dynamics models being developed using the group model building approach, for instance, for business development , for new housing development and urban renewal (Eskinasi et al, 2009) and for integrated sustainability assessments (Videira et al, 2010). Alongside these case studies, there has been a continuing focus on methodological developments, drawing upon the accumulated experience of many years of case study work Rouwette, 2011).…”
Section: Facilitated Modelling and Simulationmentioning
confidence: 99%
“…Forrester's Urban Dynamics (1969) is one of the early renowned SD works that addresses urban growth and decay. Later SD works in the housing sector focus on the effects of urban development on the social housing market (Eskinasi, Rouwette, & Vennix, 2009) and the dynamics of housing markets (Eskinasi, Rouwette, & Vennix, 2011;Özbaş, Özgün, & Barlas, 2014) from a policy perspective. From an industrial perspective, the subjects addressed include: the building supply chain (Hong-Minh & Strohhecker, 2002), competitiveness in the construction industry (Gilkinson & Dangerfield, 2013;Peace, Dangerfield, Green, & Austin, 2010), project management (Park & Pena-Mora, 2003;Parvan, Rahmandad, & Haghani, 2015), and building design and operation (Thompson & Bank, 2010).…”
Section: System Dynamics (Sd)mentioning
confidence: 99%
“…that serve as building blocks for a workshop, including action and responsibility plans. Stakeholders have been involved in participatory SD studies on topics of energy transitions (de Gooyert, Rouwette, van Kranenburg, Freeman, & van Breen, 2016;Ulli-Beer et al, 2017), city resilience (Xing, Lannon, & Eames, 2014), residential energy efficiency (Elias, 2008), and social housing market dynamics (Eskinasi et al, 2009).…”
Section: System Dynamics (Sd)mentioning
confidence: 99%
“…Accordingly, interviews and workshops with experts are commonly used in model building as they have already developed 'mental models' of cause and effect from a well-informed basis. Eskinasi et al (2009), for example, involved stakeholders and policymakers to develop an SD model in an urban transport context and found that the process yielded counterintuitive insights which may have been otherwise missed, and helped stakeholders to work through contentious issues. These collaborative approaches to model building, often referred to as Group Model Building (Vennix 1996, Luna-Reyes and Andersen 2003, Richardson 1991, all share the same underlying viewpoint that involving client groups and subject matter experts in the model building process, especially in matters of policy and strategy (Luna-Reyes et al 2006) is important but also challenging.…”
Section: Applications Of System Dynamics Modelling To Transportmentioning
confidence: 99%